Sarcasm in the Comments Column of the MedanTalk Instagram Account: A Pragmatic Study - Ariasy, Muthia Sufi; Radhiah; Trisfayani (Journal of Practice Learning and Educational Development, 2026)
This research is entitled “Sarcasm in the Comment Column of MedanTalk Instagram Account: A Pragmatic Study”. This research aims to describe the types of sarcasm and analyze the meaning of implicatures contained in the Comment Column of MedanTalk Instagram Account. The data source of this research is qualitative research. The data source of this research is comments from several posts uploaded by MedanTalk account. The data collection techniques of this research are reading techniques and note-taking techniques. The data analysis techniques of this research are data reduction, data display, conclusion drawing and verification. Based on the results of the research, four types of sarcasm were found, including propositional sarcasm (31 data), lexical sarcasm (14 data), like prefixed sarcasm (1 data), and ilocutionary sarcasm (19 data). The most dominant sarcasm is propositional sarcasm because this type is most often used by users to convey criticism or satire indirectly but still clearly. This suggests that propositional sarcasm is a primary choice in interactions in the comments section, particularly for expressing disagreement or dissatisfaction in a subtle yet pointed manner.